Evidence of a threshold size for Norwegian campsites and its dynamic growth process implications: Does Gibrat's law hold? - Robin Valenta; Johannes Idsø; Leiv Opstad (Economies, 2021)
Although campsites are an important segment of the tourist sector, few applied articles have analyzed their growth path and tested Gibrat's Law for firms within this industry. This knowledge can be of importance to the authorities when analyzing the regional impacts of growth in this sector. With government statistics from the last decade, we use a GMM framework to test the stricter version of Gibrat's Law, which consist of three parts: the campsites' growth trend, how they carry over success and failure, and how volatile their size is. The first and third part are rejected for Norwegian campsites, leading to a rejection of Gibrat's Law. To see if firms of different sizes follow different dynamics, we split the sample in three parts. Here, we find evidence of a threshold size, as large campsites follow a fundamentally different dynamic than small and medium campsites. Specifically, large campsites gain no stability in revenue by further increases in size, whereas they carry over success/failure across years. The opposite is true for the rest of the sector. Gibrat's Law is rejected on at least one count for each of the sub-samples. Lastly, we supplement the analysis with economy-wide and firm-specific variables to test further hypotheses.
Keywords: 330; tourism; campsites; dynamic panel data; Gibrat’ s Law; growth; Norway; system GMM estimator